Characteristics of the transportation structure of the transport-logistical complex and its dynamics - D. R. Abdyusheva; A. A. Stepanov (Управление)
The structure and dynamics of the transport and logistics complex transportation have been deseribed in the article. The analysis of the current state of the transport-forwarding service market allows to distinguish significant market changes in terms of improving technologies and modernizing logistics schemes. Today, transport, communications, Internet technologies, systems of customer relationship management and expeditionary infrastructure are part of human life and are type of international interaction at the global, regional and intercountry levels. The structure of the market of freight forwarding services is a complex mechanism of relations between factors and structures, that can ensure the density of the market under the influence of factors of the macroeconomic environment. In the structure of the studied forwarding, services there is a number of small systems, that fully interact with each other: industrial, market, organizational, assortment, production and technological, territorial, institutional, social and other structures.Modern Russia has a powerful, diversified, transport complex; all types of transport are represented on its territory. However, Russia is not the leader in the world market of transport and logistics services, in terms of the share of countries in world freight turnover. Russia is inferior to the positions of the United States, China and other European countries. The structure of the cargo transportation throughout the transport and forwarding complex of Russia is quite heterogeneous. The fact has been highlighted, that in the structure of transported goods a trend of growth in the volume of transportation of low-income goods against the background of a stable level of transportation volumes of high-yield cargo is observed. In terms of warehouses, Russia is also not in the lead; for expeditionary services. Russia is inferior to all European countries, but the modern development of digital technologies will help Russia reach the world level of service.